Etiology and pathogenesis of Moyamoya Disease: An update on disease prevalence. Issue 3 (April 2017) - Huang, Shuo; Guo, Zhen-Ni; Shi, Mingchao; Yang, Yi; Rao, Mingli
Moyamoya disease is a chronic cerebrovascular occlusive disease that is characterized by progressive stenosis of the terminal portion of the internal carotid artery and its main branches. The occurrence of Moyamoya disease is related to immune, genetic, and other factors. Though the research of Moyamoya disease has made great strides in the past 60 years, the etiology and pathogenesis are largely unknown. This review will focus on the genetic pathogenic and inflammation factors of Moyamoya disease.